TRANSPARENCY OF FINANCING POLITICAL ACTIVITIES: INTERNATIONAL LEGAL EXPERIENCE AND PRACTICE OF UKRAINE - Сопілко, Ірина Миколаївна; Корчак, Ярослав Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to highlight the importance of ensuring transparency in the financing of political activities, taking into account the experience of foreign countries, as well as highlighting the main problems of the implementation of domestic norms on political financing. Methods of research: analysis, studying and comparing features of ensuring transparency of financing of political activity in the experience of foreign countries and Ukraine. Results: the place and role of financing of political activity for the development of society and the state are determined, the most urgent problems are set out in terms of ensuring transparency of financing of political activities and the evaluation of the main criteria for such problems. It was clarified that the problems of ensuring the transparency of financing of political activity are not unique for Ukraine, but are global in nature for most countries of the world. Therefore, the development of uniform, current provisions regarding the transparency of funding for political activities continues to this day. Discussion: identification of the most urgent problems of ensuring transparency of financing of political activity and formulating proposals for their elimination. In modern society, the role of money is crucial in carrying out one or another activity. Funding for political activity is no exception. Unfortunately, not all citizens (especially citizens of the CIS countries) understand the true goals and purposes of political parties, and therefore the issue of their financing by such a society remains acute. That is why the purpose of this article is to reveal the essence of financing of political activity, its importance and actual problems that arise in the process of financing political activities. At the basic level, political financing has an impact on most of the most pressing aspects of political life, namely: free and fair elections; the implementation of democratic principles in politics; effective public administration; the level of political corruption. The listed components of any state system of political funding, while each of them can be carried out by political parties and countries that can be positive or negative. The availability of sufficient resources can allow electoral runners to work effectively with the electorate and address their political boundaries, but at the same time may be the reason for the dishonest electoral competition. Financial resources are needed and after the election for development of the dialogic state of the permanent population. The issue of political financing is manifested primarily in the specifics of the legislation and the legal system of the country. For example, in 2015, within the framework of anti-corruption reform, Ukraine was the first to adopt a number of changes to the current legislation in the field of financing political activities. After the adoption of these changes, many conflicts were identified, as well as problematic issues, for example: the lack of proportionality of penalties for violations, lack of normative definitions of most concepts, abuse by public persons, ambiguous interpretation of the same rules, etc. An example of Ukraine is not unique, as each country faces these problems, and the issue of eliminating existing gaps and forming common standards continues. Many international organizations, which for many years studied the features of political financing and control in a variety of conditions and situations, created a kind of list of key points that need to be taken into account when considering this area of ​​life of the state. Despite the diversity of practical experience and approaches applied by individual organizations, it is possible to highlight some of the unchanged results of all research conducted. So, in 2009, the International Foundation for Electoral Systems (IFES), along with other organizations, agreed to adopt a list of key moments regarding the role of money in politics around the world: 1) Any democratic system needs political funding and political parties must have access to funds to play their part in the political process. At the same time, the regulatory framework should not restrict healthy political competition. 2) In any political system, money always remains at risk of possible abuses, which is why it is desirable to have one or another system of regulating political finance. 3) When developing a strategy for regulating and controlling political financing, it is necessary to take into account the peculiarities of the current situation and political culture of the country. 4) Effective regulation and free access to information can help to control the potential negative effects of political funding, but only if they are well thought out and effectively applied in practice. 5) The effectiveness of the supervisory system depends on the type of activity and the degree of coordination between the stakeholders (such as public authorities, civil society and the media), while it should be based on transparency principles This article will identify the most common problems in financing political activities and their potential solutions (for example, involving public representatives, formulating common rules and regulations, forming additional institutions, etc.).